NECESSITY OF FORMATION OF SOCIO-PHILOSOPHICAL THINKING OF YOUTH IN YEARS OF INDEPENDENCE - Ruzimuratovna, Ochilov Nigor (Journal of Learning on History and Social Sciences, 2024)
Objective: This study aims to explore the role of young people in the formation and development of civil society, particularly in the context of democratic reforms and the cultivation of democratic values. Methods: The research utilizes a qualitative approach, analyzing the attitudes, perceptions, and behaviors of young individuals toward democratic processes and societal transformation. Data were collected through surveys and interviews, focusing on their understanding of democratic principles, self-awareness, civic engagement, and political participation. Results: The findings indicate that young people demonstrate a strong desire to contribute to the development of civil society. They exhibit a deep understanding of democratic reforms, a willingness to engage in new social relationships, and an evolving historical and political consciousness. Furthermore, there is a notable increase in self-confidence and a growing sense of civic responsibility, reflecting the positive outcomes of democratic changes within society. Novelty: This study highlights the emerging role of youth as active participants in the democratization process, suggesting that their involvement is a crucial factor for the successful implementation of democratic reforms and societal progress. The research contributes to understanding the relationship between youth development and political transformation in contemporary societies.